Kinerja Guru sebagai Pengembang Kurikulum 2013 - Suriswo; fikri aulia (Cakrawala: Jurnal Pendidikan, 2017)
The purpose of this study is to obtain empirical information about teacher competence, and teacher performance in planning, implementing and evaluating the curriculum 2013. The research is carried out using qualitative approach type case study. In accordance with the characteristics of the problem studied, this research activity is based on evaluative descriptive studies. Characteristics of qualitative research are characterized by activities to observe people in real situations both in the interacting environment, as well as to understand the behavior of the observed person. The location of this research is in SMP N 1 Kota Tegal Central Java Province and the subjects of this study are the principal of 1 person, 10 teachers, 1 student, vice head of curriculum 1 person in junior high school N 1 Tegal City Central Java Province From the results of this study it can be concluded that the performance of teachers as the developers of the 2013 curriculum is good but there are still many shortcomings about the understanding of the concept of learning contained in the curriculum 2013, the 2013 curriculum emphasizes the development of the character of learners, 2013 curriculum is very good for learners in developing the process of thinking and discussio.